Quantized feedback stabilization of continuous time-delay systems subject to actuator saturation. (November 2018) - Song, Gongfei; Lam, James; Xu, Shengyuan
Abstract: In this paper, the problem of quantized feedback stabilization is investigated for continuous time-delay systems subject to actuator saturation. By utilizing two different methods, delay-independent conditions are obtained to guarantee the existence of a region of admissible initial conditions from which all trajectories of the resulting closed-loop system converge to a neighborhood of the equilibrium. Furthermore, delay-dependent conditions are developed based on the delay partitioning idea and the Lyapunov–Razumikhin functional approach, respectively. Finally, several examples are provided to demonstrate the effectiveness of the proposed approaches.